Letter from the editor (2017)
Great challenges come for the world. Climatic change, clean energy, petroleum, politic points of view using science for their own benefit. During the last months, the catastrophes have been in the spotlight, not only for those who work on the sciences side to relieve the pain caused or avoid the consequences, but also those states' managers trying to reach political objectives as the earth stills moving, the water continues running through streets and housings; when the forest fires are not completely extinguished, some people is looking for economic or ideology tributes. It's part of our history. From the character Rhett Butler in Gone with the wind, the inspiring American novel, who made a vast fortune with the war, toward the contractors around the world drying public budgets as they explain the "risk management" concept. But science and politic are not going hand-in-hand.Recently, the Andean Region in South America has been the scenery of record-breaking floods and landslides; Peru was hit by heavy rains causing damages in the capital city Lima and the northern part of the country. In Colombia, the same heavy rains caused by El Niño climate cycle destroyed two neighborhoods in Mocoa, southern city capital of a department, state equivalent. Three hundreds of people died. At the same time, Bolivia is struggling with the drought consequences of climatic change. Country by country in this subcontinent the landscape is similar.  A political earthquake was the recent marches celebrated around the globe claiming for respect and support for the science. "We are marching today to remind people everywhere, our lawmakers especially, of the significance of science for our health and prosperity," said in Washington Bill Nye, a science educator with the fame of a rock star. People knows the solution for a better future is in the hands of our politicians; their decisions will allow the development or the constraint of the science. "Science, not silence," "Oceans are rising, and so are we," "Fund Science = Fun Future," "Policy without science is a Biohazard," "Science is not a partisan issue, it is the foundation of our society," "Science is NOT an opinion," were some of the messages exhibited by demonstrators in their marches.Humbly, from the Earth Sciences Research Journal, we want to adhere the same message: “It’s not magic, it’s science!” We present to you this new volume, is not so so much, but we hope every little bit helps.